Legal Assessment of the Human Rights Limitations on the Preservation of Cultural Heritage - Valiyeva, Gunel (Teisė, 2023)
This article researches the following questions: defining the protectable subject matter as cultural heritage in the International Law, the obligation to protect the cultural heritage and evaluation of the cultural heritage as a Human Rights issue. Additionally, assessment of the Human Rights-based limitations on the preservation of the cultural heritage and legal grounds for the right to destroy and its limits have been discussed. It is defined that, the obligation to protect the cultural heritage is a duty established by the International Law on the states, rather than on the non-state actors. The general approach for the assessment of the Human Rights limitations on cultural heritage protection is expected to be based on the principles of balance of interests and the limited transformation or conditionality.
Keywords: cultural heritage; preservation of cultural heritage; destruction of cultural heritage; human rights limitations on cultural heritage preservation; right to destroy